Markers of kidney tubule function and risk of cardiovascular disease events and mortality in the SPRINT trial. (30th June 2019) - Garimella, Pranav S; Lee, Alexandra K; Ambrosius, Walter T; Bhatt, Udayan; Cheung, Alfred K; Chonchol, Michel; Craven, Timothy; Hawfield, Amret T; Jotwani, Vasantha; Killeen, Anthony; Punzi, Henry; Sarnak, Mark J; et al.
Abstract: Aims: Biomarkers of kidney tubule injury, inflammation and fibrosis have been studied extensively and established as risk markers of adverse kidney and cardiovascular disease (CVD) outcomes. However, associations of markers of kidney tubular function with adverse clinical events have not been well studied, especially in persons with chronic kidney disease (CKD). Methods and results: Using a sample of 2377 persons with CKD at the baseline Systolic Blood Pressure Intervention Trial (SPRINT) visit, we evaluated the association of three urine tubular function markers, alpha-1 microglobulin (α1m), beta-2 microglobulin (β2m), and uromodulin, with a composite CVD endpoint (myocardial infarction, acute coronary syndrome, stroke, acute decompensated heart failure, or death from cardiovascular causes) and mortality using Cox proportional hazards regression, adjusted for baseline estimated glomerular filtration rate (eGFR), albuminuria, and CVD risk factors. In unadjusted analysis, over a median follow-up of 3.8 years, α1m and β2m had positive associations with composite CVD events and mortality, whereas uromodulin had an inverse association with risk for both outcomes. In multivariable analysis including eGFR and albuminuria, a two-fold higher baseline concentration of α1m was associated with higher risk of CVD [hazard ratio (HR) 1.25; 95% confidence interval (CI): 1.10–1.45] and mortality (HR 1.25; 95% CI: 1.10–1.46), whereas β2m had no association with either outcome. A two-fold higher uromodulin concentration was associated with lower CVD risk (HR 0.79; 95% CI: 0.68–0.90) but not mortality (HR 0.86; 95% CI: 0.73–1.01) after adjusting for similar confounders. Conclusion: Among non-diabetic persons with CKD, biomarkers of tubular function are associated with CVD events and mortality independent of glomerular function and albuminuria.